Work Motivation, Incentive Systems, and Job Stress as Predictors of Sales Performance in the Digital Telecommunications Sector - Rismawati, Amelia; Gusti, Yenni Kurnia (Research Horizon, 2026)
This study is motivated by the importance of improving sales performance as a key factor in achieving IndiHome marketing targets in Yogyakarta, where employee performance is influenced by internal factors such as work motivation, incentive systems, and job stress. The purpose of this research is to examine the effect of work motivation, incentive systems, and job stress on the performance of IndiHome sales personnel in Yogyakarta. A quantitative approach with an associative research design was employed, and data were collected through Likert-scale questionnaires distributed to 60 sales staff. The data were analyzed using multiple linear regression with SPSS version 23, including validity, reliability, and classical assumption tests. The results indicate that work motivation and incentive systems have a positive and significant effect on sales performance, while job stress does not have a significant partial effect. However, when examined simultaneously, work motivation, incentive systems, and job stress significantly influence the performance of IndiHome sales personnel in Yogyakarta. In conclusion, improving sales performance can be achieved by strengthening work motivation, implementing fair incentive systems, and effectively managing job stress to support optimal achievement of sales targets.